Reasonable Accommodation as a Means of Ensuring Access to Work for Persons with Disabilities in the Polish Legal System - Paluszkiewicz, Magdalena (PRAWO i WIĘŹ, 2023)
This paper describes the obligation to provide reasonable accommodation in the Polish legal system to remove barriers experienced by persons with disabilities in accessing work. The presentation of this issue will be made in the context of how the standards of the CRPD (United Nations Convention on the Rights of Persons with Disabilities) and the Employment Equality Directive are implemented in the Polish labour legislation. The concept of reasonable accommodation and the scope of entities obliged to provide it to persons with disabilities who are just seeking employment and those already in employment will be analysed. It will be followed by characterising the limits of implementing this obligation, which allows for considering the resources at the disposal of the entities obliged to provide reasonable accommodation. Finally, the author discusses the legal consequences of failure to provide reasonable accommodation and the legal remedies available to persons with disabilities in such a situation. The analysis, taking into account the body of doctrine and jurisprudence, will make it possible to indicate practical difficulties in the application of the legal regulation of reasonable accommodation and, as a result, to formulate de lege ferenda postulates.